2022
DOI: 10.1155/2022/4421418
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Examination on Risk Factors of Infertility Caused by EMT and Their Correlation with VEGF, TNF‐α, IL‐6, IL‐10, and IL‐17

Abstract: In order to explore the risk factors of infertility caused by endometriosis (EMT) and their correlation with vascular endothelial growth factor (VEGF), TNF-α, IL-6, IL-10, and IL-17, endometriosis sufferers admitted to our hospital from January 2021 to May 2022 are selected to conduct the examination. According to the pregnancy of patients, patients were included in the simple EMT set and EMT combined infertility set, with 50 cases in each group. The degree of dysmenorrhea is evaluated by the VAS score, and Lu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
0
1
0
2
Order By: Relevance
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
“…Esses dados sinalizam para provável diferença etiológica das apresentações da doença, com implicações no tratamento das entidades clínicas, o qual deve ser diferenciado(Kamergorodsky et al, 2009).Há que se considerar também que o tratamento clínico hormonal inviabiliza a correção de uma das maiores queixas associada a esta doença, que é a infertilidade. Todas essas justificativas impulsionam para a busca de alternativas ao tratamento cirúrgico e à supressão hormonal, que contemplem a As pesquisas ao longo dos anos demonstraram a associação da doença com inflamação e com níveis aumentados de citocinas(Podgaec et al., 2007; Nothnick & Alali, 2016; Riccio et al, 2018; Bellelis et al, 2019; Li & LibinWeng, 2022, Brichant et al, 2022), com provável relação direta entre os escores de dor e a concentração desses mediadores inflamatórios(Li & LibinWeng, 2022), o que corrobora a hipótese de que a maior parte da dor associada à endometriose é de origem inflamatória(Howard, 2009;Brichant et al, 2022). O aumento das citocinas se deve à produção exacerbada tanto por células do sistema imune, quanto pelo próprio tecido endometriótico(Nothnick & Alali, 2016).…”
unclassified
“…Um mecanismo que pode ser implicado nessa produção aumentada de citocinas é a resposta alterada à progesterona observada em algumas mulheres, por expressão reduzida de receptores para este hormônio. Neste caso, haveria uma resistência à ação das drogas e, desta forma, a ação antiinflamatória da progesterona, responsável pela redução da dor, não seria observada(Nothnick & Alali, 2016).Outros incluem as interleucinas 1, 6, 8, 10 e 17 (IL-1, IL-6, IL-8, IL-10 e IL-17), o fator de crescimento neural (NGF), a prostaglandina F2-alfa e os mastócitos(Howard, 2009;Riccio et al, 2018;Malvezzi et al, 2019;Li & LibinWeng, 2022). hérnia umbilical, dolicocefalia, alveolite fibrosante, atresia de válvula pulmonar, anencefalia, craniossinostose, microcefalia, tetralogia de Fallot, deficiências em membros e sindactilia(Walden et al, 1979;Hyoun et al, 2012;Verbene et al, 2019).…”
unclassified